Urban Tourism: Designing a Tourism Space in the Post-war City Context for Sustainability: https://doi.org/10.36777/jag2023.2.2.1 (Journal of Asian Geography, 2023)
Tourism is viewed as a tool for poverty alleviation, economic diversification and regeneration, multilateral integration and peace, post-conflict stability, and socio-economic recovery in many post-conflict nations. Urban tourism is one of the forms that has emphasized the importance of supporting urban sustainability while considering all of the city's dynamic change processes, such as natural resource protection, culture, architecture, and environmental management. The purpose of this study is to assess the issues and challenges that confront urban tourism development and to make recommendations for developing sustainable urban tourism in Jaffna City. This study incorporated both primary and secondary data. Direct field observation, structured questionnaire surveys, focus group discussions, and key informant interviews were used to collect the necessary primary data. Secondary data was gathered from authorized statistical reports. The collected data was analyzed using descriptive statistical methods, and a SWOT analysis was performed to determine Jaffna's strengths, weaknesses, opportunities, and threats to sustainable urban tourism development. The maps for the study were created using the ArcGIS 10.4 software. According to the study's findings, ineffective green environmental protection systems, inadequate infrastructure facilities, a lack of industrial professionalism, cultural barriers to tourism promotion, ineffective marketing promotional strategies, a lack of institutional coordination, and a lack of tourist product diversification are the factors posing challenges to Jaffna city's sustainable urban tourism development. Based on the strengths, weaknesses, opportunities, and threats of Jaffna's urban tourism development, this study provided recommendations for sustainable tourism development that will assist different stakeholders in rethinking Jaffna's urban tourism in a sustainable manner.